THEATER OF CORYPHAEUS AND "BEREZIL" THEATER IN THE WORKS OF LITERARY CRITICS OF THE UKRAINIAN DIASPORA - Лущій, С. (Київський національний університет імені Тараса Шевченка, 2021)
The article considers the issue of reception of creativity of the theater of coryphaeus and the theater "Berezil" in the literary studies of the Ukrainian diaspora in the second half of the twentieth century. The material for the research was articles and radio broadcasts by Yu. Lavrinenko, literary explorations by Yu. Sherekh and M. Pavlyshyn. The study also deals with emigrant productions of plays performed by the "Berezil" Theater in Soviet Ukraine, and directorial interpretations of Shakespeare's plays by P. Saksagansky. The article explains why diaspora researchers paid more attention to the Berezil Theater than to the Coryphaeus Theater. Lavrinenko's radio programs dedicated to outstanding figures of theatrical art are analyzed. The plays of coryphaeus playwrights directed by the diaspora are considered. Information on the productions of the Les Kurbas Theater (Australia) by I. Karpenko-Kary, M. Starytsky, M. Kropyvnytsky is provided. Yu. Lavrinenko and Yu. Sherekh were well acquainted with the performances of the Berezil Theater. Therefore, the article presents their memories about Les Kurbas. A new re-reading of M. Starytsky's works by directors of the diaspora is considered. The reasons for the popularity of the works of classic playwrights among the audience of the diaspora are found out. In articles and radio programs Yu. Lavrinenko, Yu. Sherekh and M. Pavlyshyn added unknown touches that helped to present outstanding figures of dramatic art more vividly, colorfully and more fully. Memories and unknown archival sources are used in the work.

Розглянуто питання рецепції творчості театру корифеїв та театру "Березіль" у літературознавстві української діаспори другої половини ХХ ст. Матеріалом для дослідження стали статті й радіопередачі Ю. Лавріненка, літературознавчі розвідки Ю. Шереха та М. Павлишина. Йдеться також про еміграційні постановки спектаклів, здійснені театром "Березіль" у радянській Україні, про режисерські інтерпретації П. Саксаганським п'єс В. Шекспіра. Розглядається нове перепрочитання творів М.П. Старицького режисерами діаспори. З'ясовано причини популярності творів драматургів-класиків у глядачів діаспори. У роботі використано спогади та невідомі архівні джерела.
ТЕАТР КОРИФЕЇВ І ТЕАТР "БЕРЕЗІЛЬ" У ПРАЦЯХ ЛІТЕРАТУРОЗНАВЦІВ УКРАЇНСЬКОЇ ДІАСПОРИ
Keywords: theater of coryphaeus; theater "Berezil"; reception; diaspora; national identity; modernism; театр корифеїв; театр "Березіль"; рецепція; діаспора; національна ідентичність; модернізм